ANALISIS PENGARUH BELANJA PEMERINTAH DAN PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN DI INDONESIA - DAHIRI; ADHI WIBOWO (Pusat Kajian Anggaran, 2016)
This study purpose to show the relationship between government spending and economic growth to poverty in Indonesia. With central and local government spending tends to increase every year. However, the increase can not guarantee it will decline against poverty. The spending there is related directly and indirectly to poverty. National and regional economic growth is a reflection of the relationship that indirect expenditure against poverty. The results of the study with time series data and panel data years 1984-2015 all provinces in 2013-2015, the model 1 and 2 show that the central and local government spending and the national and regional economic growth significantly affects poverty with a negative relationship.